Peningkatan Kemampuan Berbicara Siswa Melalui TENANT dan Objek Nyata - Syaifullah Syaifullah; Ribut Wahyu Eriyanti; Atok Miftachul Hudha (AL-DALIL: Jurnal Ilmu Sosial, Politik, dan Hukum, 2023)
At English Education Department of Education and Vocational Studies Faculty of Universitas Lancang Kuning, it was found that the students had low speaking skills. One of the factors is the students’ hesitation in making mistakes, especially mistakes in grammar. It was Classroom Action Research (CAR). The aimed of this research was to improve the students’ low speaking skills by using TENANT (Teaching English with Natural Acting and Natural Talking) and Real Object. This research had been carried out since February until April 2022. It had three cycles and five meetings within it. There were 24 students all of them who were taught to speak English by using TENANT and Real Object. It was found that there was improvement of the students’ speaking skills under the use of TENANT and Real Object which were based on the students’ speaking based score with their scores from cycle I, II, and cycle III. In conclusion, TENANT and Real Object can help the students to improve their speaking skills. This finding implies that the use of TENANT and Real Object can be used to enhance the students’ speaking skill in English speaking class.